Beauty Standard for New Normal: What Indonesian Beauty Advertising Tell Us? - Dana Afriza (ADI Publisher, 2020)
This paper aims to examine how beauty product brand advertisements adapt to new habits due to the Covid-19 pandemic. A brand list of 295 brands was compiled. The keyword